1997
DOI: 10.1002/(sici)1096-8628(19970725)74:4<398::aid-ajmg11>3.3.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Personality and language characteristics in parents from multiple‐incidence autism families

Abstract: Several studies have suggested that the genetic liability for autism may be expressed in non-autistic relatives of autistic probands, in behavioral characteristics that are milder but qualitatively similar to the defining features of autism. We employ a variety of direct assessment approaches to examine both personality and language in parents ascertained through having two autistic children (multiple-incidence autism parents) and parents of Down syndrome probands. Multiple-incidence autism parents had higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
178
1
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(196 citation statements)
references
References 8 publications
(8 reference statements)
12
178
1
5
Order By: Relevance
“…When narrating, individuals with ASD fail to provide causal explanations to describe actions, experiences, and emotions (Capps, Losh, & Thurber, 2000; Diehl et al., 2006; Losh & Capps, 2003; Tager-Flusberg, 1995) and have difficulty adopting the perspectives of others (García-Pérez, Hobson, & Lee, 2008). Because subclinical pragmatic difficulties are also seen in relatives of individuals with ASD as part of the broad autism phenotype, pragmatic impairment is hypothesized to represent a genetically meaningful trait marking vulnerability to ASD (Landa et al, 1992; Losh, Childress, Lam, & Piven, 2008; Piven, Palmer, Landa, Santangelo, & Childress, 1997). …”
Section: Pragmatic Language In Autism Spectrum Disorder and Fragile Xmentioning
confidence: 99%
“…When narrating, individuals with ASD fail to provide causal explanations to describe actions, experiences, and emotions (Capps, Losh, & Thurber, 2000; Diehl et al., 2006; Losh & Capps, 2003; Tager-Flusberg, 1995) and have difficulty adopting the perspectives of others (García-Pérez, Hobson, & Lee, 2008). Because subclinical pragmatic difficulties are also seen in relatives of individuals with ASD as part of the broad autism phenotype, pragmatic impairment is hypothesized to represent a genetically meaningful trait marking vulnerability to ASD (Landa et al, 1992; Losh, Childress, Lam, & Piven, 2008; Piven, Palmer, Landa, Santangelo, & Childress, 1997). …”
Section: Pragmatic Language In Autism Spectrum Disorder and Fragile Xmentioning
confidence: 99%
“…The broad autism phenotype (BAP) refers to heritable, subclinical traits that are often seen among unaffected relatives of individuals with autism (Bolton et al, 1994, Losh et al, 2008, Piven et al, 1997b, Piven et al, 1997a, Szatmari et al, 2000). The features of the BAP are qualitatively similar to the core communication, social, and restricted/repetitive domains of the autism triad.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these, it has been shown that distinct personality domains exist in ASD parents (Austin 2005Bolton et al 1994Micali et al 2004;Murphy et al 2000;Pickles et al 2000;Piven et al 1997). Th us, such personality features may be inherited as autistic phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Th e broad autism phenotype (BAP) refers to heritable, subclinical traits that are oft en seen among unaff ected relatives of individuals with autism (Bolton et al 1994;Losh et al 2008;Piven et al 1997;Szatmari et al 2000). Th e features of the BAP are qualitatively similar to the core communication, social, and restricted/repetitive domains of the autism triad.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation